My parents think I'm sleeping - Prelutsky, Jack.; Abolafia, Yossi (New York : HarperCollins, 2007)
Contains fourteen, humorous poems about bedtime.
My parents think I'm sleeping -- Tonight is impossibly noisy -- The clouds I watched this afternoon -- Night is here -- A spooky sort of shadow -- What happens to the colors? -- I have been in bed for hours -- Chocolate cake -- Rain -- It is so still -- If it was sunlight shining -- When I'm very nearly sleeping -- A million candles -- I'm awake! I'm awake!
"3, reading alone.".
Originally published: Greenwillow Books, 1985.
Horn Book.
Kirkus Review.
4.6
K-3
Keywords: Children's poetry, American; Sleep -- Juvenile poetry; American poetry; Sleep -- Poetry; American poetry; Sleep -- Poetry; Readers (Elementary).